First Report of Enteric Red Plague of Oreochromis Niloticus (Cichlidae) And Cyprinus Carpio (Cyprinidae) Reared in Cameroon: Mortality Rate, Risk Factors and Financial Loss - Georges, Fonkwa; Jacques, Nack; Julius, Awah Ndukum; Cedric, Yamssi; Minette, Tomedi Eyango; Tchoumboue, - (Research in Agriculture Livestock and Fisheries, 2023)
Diseases are among the major constraints to sustainable aquaculture. Fish pathogens include bacteria responsible for devastating effects on the fish health and even that of consumers. In Cameroon, there is a dearth of quantitative data related to fish diseases and the economic impact. An epidemiological survey was carried out from April 22 to May 23, 2021 during a first epizootic of the enteric red plague in the fishes Oreochromis niloticus and Cyprinus carpio reared in ponds in the Monatélé Subdivision of the Centre Region of Cameroon. The objective was to assess clinical disorders and mortality rate, associated risk factors and economic losses in semi-intensive farms due to red plague in Cameroon. So, the standard epidemiological procedures were used to assess the mortality rates before and after antibiotic (Oxytetracyclin) treatment of the disease. Results showed that clinical signs recorded within three months of observing included lateral recumbency, breathing difficulties (dyspnea) and wide opening of mouths of affected fish. The overall mortality rate of 7.74% (294 dead fishes out of 3800) was recorded. The mortality rate was significantly higher (p < 0.001) in polyculture pond (11.33%) compared to monoculture pond (4.70%). Cyprinus carpio was significantly more affected than Oreochromis niloticus. The mortality rate was higher (p < 0.01) in younger fishes than older ones and was sex independent. The therapy was more effective in monoculture pond than in polyculture pond and in Oreochromis niloticus compared to Cyprinus carpio. Females were more sensitive to antibiotic treatment than males. The direct financial loss was $420.50. This study revealed that the main risk factors of the red plague disease were farming practice, species, age and size of fish. Rigorous epidemiological surveillance of fish diseases was suggested for improved productivity of fish farms in Cameroon. Vol. 9, No. 3, December 2022: 323-335